MENETAPKAN HUKUMAN HUDUD DENGAN METODE QIYAS - Watni Marpaung (Islamijah: Journal of Islamic Social Sciences, 2022)
The debate of opinions in fiqh studies is an ongoing study to be discussed. The birth of various schools of thought in the field of fiqh is a reflection of the diversity of understanding of the scholars of the texts of the Qur'an and Hadith. Interestingly, the difference is not only in the study of fiqh but in what is more important, namely the method of legal istinbat. In this case, Hanafi and Syafii fiqh have different views when applying qiyas to determine hudÅ«d punishments. For hanafi that qiyas cannot be used in determining hudud punishment, on the other hand for Syafi'i fiqh that qiyas can be used to determine hudud.Keywords:Â Qiyas, hudud